INCLUSIVE INSTRUCTIONAL STRATEGIES FOR A FASHION PRACTICUM COURSE IN UNIVERSITY - Siti Zahro; Didik Nurhadi; Tri Sagirani; Hany Mustikasari (Universitas Negeri Yogyakarta, 2026)
The challenges of implementing inclusive vocational education for students with special educational needs in higher education are increasingly complex, particularly in a practice-based fashion course that requires technical and procedural competencies. This study aims to examine instructional strategies for students with special educational needs in a fashion practicum course. A classroom action research design employing a Longitudinal Quasi-Qualitative approach was conducted over one semester, involving three students categorized into mild, moderate, and severe levels of need. Data were collected through participant observation, in-depth interviews, and documentation, using observation checklists, semi-structured interview guides, and field notes. The research procedure followed iterative cycles of planning, implementation, observation, and reflection. Data were analyzed thematically to identify patterns in instructional practices and student responses. The findings indicate that a uniform instructional approach implemented in the first cycle was ineffective, particularly for students with moderate and severe needs, due to a mismatch between task demands and learner characteristics. In contrast, the second cycle, which incorporated differentiated tasks, simplified instructions, and personalized sensory stimuli, significantly improved student engagement and learning accessibility. This study concludes that effective inclusive vocational education requires adaptive instructional design that integrates cognitive, emotional, and sensory dimensions, and highlights the potential of adaptive learning ecosystems to enhance sustainable inclusion and work readiness.